Improving collaborative learning in online software engineering education. (2nd November 2017) - Neill, Colin J.; DeFranco, Joanna F.; Sangwan, Raghvinder S.
ABSTRACT: Team projects are commonplace in software engineering education. They address a key educational objective, provide students critical experience relevant to their future careers, allow instructors to set problems of greater scale and complexity than could be tackled individually, and are a vehicle for socially constructed learning. While all student teams experience challenges, those in fully online programmes must also deal with remote working, asynchronous coordination, and computer-mediated communications all of which contribute to greater social distance between team members. We have developed a facilitation framework to aid team collaboration and have demonstrated its efficacy, in prior research, with respect to team performance and outcomes. Those studies indicated, however, that despite experiencing improved project outcomes, students working in effective software engineering teams did not experience significantly improved individual achievement. To address this deficiency we implemented theoretically grounded refinements to the collaboration model based upon peer-tutoring research. Our results indicate a modest, but statistically significant ( p = .08), improvement in individual achievement using this refined model.